KONSEP PENDIDIKAN ANAK DALAM PERPEKTIF AL-QUR’AN (Surat Luqman Ayat 12-19) - Nafi’in, Jami’un; Yasin, Muhamad; Tohari, Ilham (Edudeena : Journal of Islamic Religious Education, 2017)
Astract: Along with the development of the increasingly blind to the globlasasi that a lot of negatively affect the child. Beliefs that can stem this negative impact, therefore Islamic education is very necessary in this case. And the authors chose the letter Luqman verses 12-19 because in it is full of advice to build morals and increase faith in the child. The results showed that: (1) The concept of children's education. (2) The concept of children's education in the perspective of Qur'an letter Luqman verses 12-19 illustrates the emphasis of the material and methods of children's education. Educational materials that are taught include education of aqidah, shariah, and morals. The method used is with maw'idah (advice). (3) Actualization of the development of the concept of education of children in this era of globalization is to develop Islamic life-based curriculum life skill, Applying contextual approach of learning PAI on the aspect of faith, Implementing the integration of faith with science and technology. Abstrak: Seiring dengan perkembangan zaman yang semakin membabi buta kearah globlasasi yang banyak sekali berpengaruh negatif pada diri anak. Keimanan yang dapat membendung dampak negatif ini, Maka dari itu pendidikan Islam sangat diperlukan dalam kasus ini. Dan penulis memilih surat Luqman ayat 12-19 karena didalamnya sarat akan petuah untuk membangun akhlak serta meningkatkan keimanan terhadap diri anak. Hasil penelitian menunjukkan bahwa: (1) Konsep pendidikan anak. (2) Konsep Pendidikan Anak dalam perspektif Al-Qur’an surat Luqman ayat 12-19 menggambarkan penekanan materi dan metode pendidikan anak. Materi pendidikan yang diajarkan meliputi pendidikan akidah, syariah, dan akhlak. Adapun metode yang digunakan adalah dengan maw’idah (nasihat). (3) Aktualisasi pengembangan konsep pendidikan anak di era globalisasi ini adalah dengan melakukan pengembangan kurikulum agama Islam berbasis life skill, Melakukan pendekatan kontekstual pembelajaran PAI pada aspek keimanan, Menerapkan pengintegrasian iman dengan IPTEK.